2022
DOI: 10.3390/cells11162494
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins: Emerging Therapeutics for Vascular Dysfunction

Abstract: Vascular diseases account for a significant number of deaths worldwide, with cardiovascular diseases remaining the leading cause of mortality. This ongoing, ever-increasing burden has made the need for an effective treatment strategy a global priority. Recent advances in regenerative medicine, largely the derivation and use of induced pluripotent stem cell (iPSC) technologies as disease models, have provided powerful tools to study the different cell types that comprise the vascular system, allowing for a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…In contrast, qPCR data demonstrated that RNA-binding protein Quaking (QKI) may be involved in circXPO1 biogenesis, and its increased expression was positively associated with the elevated level of circXPO1 (data not shown). Since the QKI has multiple alternatively spliced isoforms [ 38 ], our next research will focus on which QKI protein is involved in the production mechanism of circXPO1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, qPCR data demonstrated that RNA-binding protein Quaking (QKI) may be involved in circXPO1 biogenesis, and its increased expression was positively associated with the elevated level of circXPO1 (data not shown). Since the QKI has multiple alternatively spliced isoforms [ 38 ], our next research will focus on which QKI protein is involved in the production mechanism of circXPO1.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, correcting pathogenic mutations in RBPs or manipulating their activity has the strong potential to rescue cardiomyopathy or promote cardiac regeneration after myocardial injury [ 27 , 28 , 29 ]. Therefore, RBPs have emerged as promising targets for therapeutic interventions for cardiovascular dysfunction [ 26 , 30 ]. Recent studies have not only further established the causal relationship between RBPs and cardiomyopathies but have also provided novel insights into the mechanism underlying disrupted cardiomyocyte structural and functional gene expression due to RBP dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…RBPs execute their regulatory functions by forming ribonucleoprotein complexes (or interactomes) by interacting with RNA in a dynamic and combinatorial manner. These interactomes may also contain RNA modifying enzymes which can influence RNA-protein interactions and ultimately drive RBP-dependent regulation of RNA stability, alternative polyadenylation and splicing, subcellular localization, and translation of mature mRNAs by ribosomes ( Park et al, 2011 ; Gilbert et al, 2016 ; de Bruin et al, 2017 ; Hoernes and Erlacher, 2017 ; Hentze et al, 2018 ; Cornelius et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, RNA binding protein with multiple splicing (RBPMS), which significantly impacts myofibrillar organization and calcium handling through alternative splicing of regulators such as titin, Pdlim5 and nexilin ( Akerberg et al, 2022 ; Gan et al, 2022 ). Similarly, the Quaking (QKI) family of RBPs function as alternative splicing factors of sarcomere and cytoskeletal component genes, calcium-handling genes, and post-transcriptional regulators ( Kelaini et al, 2021 ; Cornelius et al, 2022 ). QKI isoforms themselves are products of alternative splicing with roles in angiogenesis, cell migration and adhesion senescence ( Montañés-Agudo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%